Security and Intelligent Information Systems International Joint Confererence, SIIS 2011, Warsaw, Poland, June 13-14, 2011, Revised Selected Papers - Bouvry, Pascal; Klopotek, Mieczyslaw A.; Leprevost, Franck; Marciniak, Malgorzata; Mykowiecka, Agnieszka; Rybinski, Henryk (Information Systems and Applications, incl. Internet/Web, and HCI, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the Joint Meeting of the 2nd Luxembourg-Polish Symposium on Security and Trust and the 19th International Conference Intelligent Information Systems, held as International Joint Confererence on Security and Intelligent Information Systems, SIIS 2011, in Warsaw, Poland, in June 2011. The 29 revised full papers presented together with 2 invited lectures were carefully reviewed and selected from 60 initial submissions during two rounds of selection and improvement. The papers are organized in the following three thematic tracks: security and trust, data mining and machine learning, and natural language processing.